The Challenges of Managing Pediatric Diabetes and Other Endocrine Disorders During the COVID-19 Pandemic: Results From an International Cross-Sectional Electronic Survey - Elbarbary, Nancy Samir; dos Santos, Tiago Jeronimo; de Beaufort, Carine; Wiltshire, Esko; Pulungan, Aman; Scaramuzza, Andrea Enzo (Frontiers in Endocrinology, 2021)
Background Frequency, dimensions, management, and outcomes of the COVID-19 pandemic in children with endocrine disorders and diabetes were assessed. Methods A cross-sectional electronic survey was distributed to the global network of endocrine societies. Respondents’ professional and practice profiles, clinic sizes, their country of practice, and the impact of COVID-19 on endocrine diseases were investigated. Results Respondents from 131 pediatric endocrine centers in 51 countries across all continents completed the survey. Routine check-ups and education were altered in most pediatric endocrine clinics. Over 20% of clinics experienced a shortage of critical medications or essential supplies. ICU treatment was required for patients with diabetes and COVID-19 in 21.2% of centers. In diabetes, 44% of respondents reported increased diabetic ketoacidosis episodes in newly diagnosed cases and 30% in established cases. Biopsychosocial and behavioral changes were explicitly reported to be occurring among pediatric patients with endocrine disorders. Conclusions This large global survey conducted during the COVID-19 pandemic highlights that diabetes is more challenging to manage than any other pediatric endocrine disorder, with an increased risk of morbidity. Psychological distress due to COVID-19 needs to be recognized and addressed. The importance of close contact with healthcare professionals should be emphasized, and medical supplies should be readily available to all patients.